THE ROLE OF ECO-TOURISM DESTINATIONS IN THE DEVELOPMENT OF TOURISM. IN CASE OF BUKHARA, SHAFIRKAN DISTRICT - Nilufar, Omonova; Ruxangiz, Mavlonova (Центр Научных Публикаций (buxdu.uz), 2024)
The article discusses the overview of ecotourism, which allows Uzbekistan to take a strong position in the international ecotourism services market, which is competitive in the world community. The possibilities of integration into the world trends of the development of tourism services and the growth trends of Uzbekistan are being studied in this short research paper. The advantages of the ecotourism zones of our country, the success of the ecotourism sector in the implementation of state programs to attract ecotourists and encourage foreign investments are analyzed. The importance of using the experience of ecotourism developed countries is emphasized. Therefore, this work is dedicated to those who are intended to take a deep glance at the most prosperous and promising type of tourism in Uzbekistan.